2021
DOI: 10.1002/jev2.12123
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐encoded microproteins: A new form of cargo in cell culture‐derived and circulating extracellular vesicles

Abstract: Advancements in omics-based technologies over the past few years have led to the discovery of numerous biologically relevant peptides encoded by small open reading frames (smORFs) embedded in long noncoding RNA (lncRNA) transcripts (referred to as microproteins here) in a variety of species. However, the mechanisms and modes of action that underlie the roles of microproteins have yet to be fully characterized. Herein, we provide the first experimental evidence of abundant microproteins in extracellular vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…FuncPEP, ncEP, and cncRNAdb curated experimentally validated peptides encoded by noncoding RNAs, including lncRNAs, circRNAs, and miRNAs. SmProt collected peptides shorter than 100 mino acids (aa) identified from ribosome profiling data, literature, or MS, but no peptides longer than 100 aa encoded by lncRNAs were included ( Lun et al, 2020 ; Meng et al, 2020 ; Cai et al, 2021 ). Compared to these existing databases of noncoding RNA-encoded peptides, LncPep is focused on lncRNAs and has four advantages: 1) both validated and predicted lncRNA-encoded peptides are included in LncPep; 2) abundant evidence and detailed annotations are supplied to support peptides and lncRNAs; 3) LncPep does not have a length limitation for peptides, and peptides longer than 100 aa are also important, which has been reported by multiple studies; and 4) the “Predict” and “Blast” modules will help users to explore novel lncRNAs and peptides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FuncPEP, ncEP, and cncRNAdb curated experimentally validated peptides encoded by noncoding RNAs, including lncRNAs, circRNAs, and miRNAs. SmProt collected peptides shorter than 100 mino acids (aa) identified from ribosome profiling data, literature, or MS, but no peptides longer than 100 aa encoded by lncRNAs were included ( Lun et al, 2020 ; Meng et al, 2020 ; Cai et al, 2021 ). Compared to these existing databases of noncoding RNA-encoded peptides, LncPep is focused on lncRNAs and has four advantages: 1) both validated and predicted lncRNA-encoded peptides are included in LncPep; 2) abundant evidence and detailed annotations are supplied to support peptides and lncRNAs; 3) LncPep does not have a length limitation for peptides, and peptides longer than 100 aa are also important, which has been reported by multiple studies; and 4) the “Predict” and “Blast” modules will help users to explore novel lncRNAs and peptides.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been regarded as “junk RNAs” and have no potential to encode functional proteins. Recently, a growing amount of evidence has demonstrated that lncRNAs are able to encode functional peptides that play vital roles in physiological processes ( Anderson et al, 2015 ; Matsumoto et al, 2017 ; Anastasia et al, 2019 ; Niu et al, 2020 ; Cai et al, 2021 ; Zhang et al, 2021 ). For example, the translated peptides from lncRNA Aw112010 are essential for the orchestration of mucosal immunity during bacterial infection and colitis ( Jackson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soda et al, have recently demonstrated that HOTAIR can be detected from plasma samples using electrochemical detection, and they propose that this assay could be used in a clinical setting for the detection of various lncRNA biomarkers [172]. It is also possible to detect microproteins encoded by lncRNAs in the extracellular vesicles in human plasma samples, and these microproteins could be used as diagnostic markers [252]. More studies of different circulating biomarkers in OCs are needed to assemble a good panel of miRNA/lncRNA targets for the diagnosis of OC and for determining their response to therapy.…”
Section: Circulating Lncrnas As Diagnostic and Prognostic Biomarkers For Ocsmentioning
confidence: 99%
“…Besides, exosomes encapsulate various cargoes, including nucleic acids, proteins, lipids, and metabolites ( Kowala et al, 2016 ; Mathieu et al, 2021 ). The contents of exosomes could be up- or down-regulated due to cell types or carcinogenesis ( Cai et al, 2021 ). Such heterogeneity makes the isolation and enrichment of exosomes a challenging task.…”
Section: Introductionmentioning
confidence: 99%